Pemahaman Konsep Matematika melalui Model Pembelajaran Berdiferensiasi pada Kelas 5 Sekolah Dasar - Hermawan, Robby; Trisnawaty, Wulan; Tisngati, Urip (PGSD STKIP PGRI Pacitan, 2025)
This study aims to describe the activities of teachers and students in the application of differentiated learning and understanding of mathematical concepts in grade 5 students of SD Negeri 1 Sirnoboyo. This descriptive research was carried out in the even semester of the 2023/2024 academic year. Data was collected through observation, tests, interviews, and documentation, then analyzed using data reduction, data presentation, and conclusion drawn. The results of the study showed that: (1) Teachers' activities in the application of differentiated learning models have been carried out well in the aspects of student readiness, content differentiation, and product differentiation; (2) Student activities are also in accordance with aspects of student readiness, content differentiation, and product differentiation; (3) The understanding of mathematical concepts of grade 5 students of SD Negeri 1 Sirnoboyo after the application of the differentiated learning model showed that is generally good and quite good. Students are able to represent the concepts learned, solve mathematical problems, and present mathematical statements orally and in writing in various forms of representation. However, some students still need further guidance and practice.